CLUSTER ANALYSIS OF Callosciurus notatus, C. orestes AND C. prevostii (ORDER RODENTIA, SUBFAMILY SCIURINAE) IN SARAWAK - Wong, Siew Fui (Universiti Malaysia Sarawak, (UNIMAS), 2007)
The genus Callosciurus consists of five species, namely Callosciurus baluensis, C. prevostii, C. orestes, C. notatus and C. adamsi. This study describes the morphometric variations within the genus using existing specimen and data from Sarawak. Field sampling were conducted at Bako National Park, Satang Island and Batang Ai National Park. Cage traps subjectively selected and set for three days. Samples from Zoological Museum at Universiti Malaysia Sarawak and Sarawak Museum were applied in this study. A total of 33 specimens were examined based on 16 morphometrics characteristic (external body, skull and dental). All 16 parameters were analyzed using the discriminant function analysis (DFA) and canonical variate analysis (CVA). Two functions have been extracted from the DFA where the highest characters were observed in Function 1, namely, dietary length (DL) and Function 2, namely, tail (T), zygomatic width (ZW), bulla length (BL), cranial width (CW) and condoylobasal length (CBL). Cluster analysis was used to confirm the grouping of all samples into two groups, with the first group was C. notatus and C. oresles and the second group was C. prevostii.